Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Pembudidaya Ikan Air Tawar Di Kabupaten Lima Puluh Kota - Mukhlis, Mukhlis; Kasim, Nur Alam; Primadini, Vivin; Irmawan, Fadly; Merdekawati, Dewi; Yunita, Nurul Fatimah; Sigiro, Oktavia Nurmawaty; Kristiningsih, Ari; Maruka, Safriyanto S; Dhandy, Rahmat; Ramli, Taufik Hadi (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
The fisheries sector is one sector that has great potential in improving the economy. To increase the income of fish cultivators, farmers need to manage their business results better before they were marketed or sold. The welfare level of fish farmers was still low, this is not because the selling price of fish is low, nor is it because of the large number of imported fish, but rather due to the government's lack of attention to the fishery sector, especially freshwater fisheries. This study used a descriptive method, which was conducted in the Lima Puluh Kota Regency. The selection of the research area was carried out in purposive method. Determination of the research sample using the snowball sampling method. Collecting data using interview method using questionnaires to obtain primary data and documentation method to obtain secondary data. The data analysis method used descriptive qualitative analysis and quantitative analysis using a triangulation technique approach that tested the validity of the data using methods, sources, and theories. The results showed that the factors that significantly influenced the income of fish farmers in Nagari Andaleh, Luak District, Lima Puluh Kota Regency were the number of harvests (X1), land area (X2), production costs (X5), and the selling price of production (X6).Â While the factors that do not affect the income of rice farmers are farmer education (X3), farmer age (X4) and other occupations (X7).